2021
DOI: 10.1155/2021/8100298
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Nerve Stem Cells Loaded with FTY720 Promote the Recovery after Spinal Cord Injury in Rats by PTEN/AKT Signal Pathway

Abstract: Background. Spinal cord injury (SCI) remains a challenge owing to limited therapies. The exosome of neural stem cells (NSCs-Exos) and FTY720 transplantation could improve SCI effectively. However, the effect and mechanism of NSCs-Exos combined with FTY720 (FTY720-NSCs-Exos) transplantation in the treatment of SCI are not fully understood. Methods. Sprague Dawley rats (8-week-old) were used to establish the SCI model, followed by the treatment of NSCs-Exos, FTY720, and FTY720-NSCs-Exos. The effect of FTY720, NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…It has been demonstrated that FTY720 could inhibit the proliferation of glomerular mesangial cells by inducing cell cycle arrest and apoptosis, possibly via the regulation of the expression of cell cycle-related genes and BAX/BCL-2 ( 47 ). In addition, exosomes could ameliorate the morphology of neurons, reduce inflammatory infiltration and edema, decrease the expression of BAX and AQP-4, upregulate the expression of claudin-5 and BCL-2 and inhibit cell apoptosis ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that FTY720 could inhibit the proliferation of glomerular mesangial cells by inducing cell cycle arrest and apoptosis, possibly via the regulation of the expression of cell cycle-related genes and BAX/BCL-2 ( 47 ). In addition, exosomes could ameliorate the morphology of neurons, reduce inflammatory infiltration and edema, decrease the expression of BAX and AQP-4, upregulate the expression of claudin-5 and BCL-2 and inhibit cell apoptosis ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the included 32 studies, only two studies were controlled studies ( 29 , 33 ), and the remaining 30 studies were randomized controlled studies. The species of animals included SD rats ( 19 21 , 28 37 , 39 , 40 , 42 44 , 46 , 47 , 49 53 , 55 , 56 ), Wistar rats ( 41 , 54 ), and C57BL/6 mice ( 38 , 45 , 48 ); gender included male ( 28 , 30 32 , 38 45 , 49 , 53 , 54 ) and female ( 19 , 20 , 29 , 33 , 34 , 36 , 37 , 46 48 , 50 52 , 55 , 56 ), two studies did not report the sex of the animals ( 21 , 35 ); the weights of animals were between 150 ( 41 ) and 300 g ( 20 , 44 ), the weight of the mouse was between 17 and 22 g ( 48 ), and seven of the studies did not report the weight of the animals ( 21 , 29 , 30 , 38 , 42 , 45 , 50 ); age was between 6 ( 38 , 44 , 45 , 50 , 51 ) and 12 weeks ( 47 , 56 ), and nine of the studies did not report the age of the animals ( …”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported types of exosomes but did not report specific sources ( 31 , 32 , 38 , 40 , 45 , 46 ). The transplantation route of exosomes included tail vein ( 19 21 , 29 32 , 34 50 , 52 – 56 ), intranasally ( 33 ) and subcutaneous ( 51 ), and one study did not report the route of exosome transplantation ( 28 ); the time transplantation of exosome ranged from 0 ( 19 , 20 , 31 , 38 , 41 , 44 47 , 49 ) to 24 h ( 42 , 43 ) after modeling, one study did not report the time of exosome transplantation ( 40 ); dose of exosomes ranged from 20 ( 29 ) to 200 μg ( 28 , 30 33 , 36 38 , 41 , 43 , 45 49 , 53 , 56 ); the control group includes PBS ( 19 21 , 28 32 , 34 , 35 , 38 , 39 , 41 , 43 51 , 53 – 56 ), saline ( 33 , 36 , 37 , 40 , 42 ), and blank ( 52 ). Basic information of the study subjects was summarized in Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations